1990
DOI: 10.1177/019262339001800123
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Blood-Nerve Barrier in Experimental Nerve Edema

Abstract: Nerve edema is a common response to the nerve injury seen in many peripheral neuropathies and is an important component of Wallerian degeneration. However, independent pathologic effects of nerve edema that aggravate or induce nerve injury extend the role of edema beyond that of an epiphenomenon of injury. New insights into the mechanism and impact of nerve edema come largely from animal models. In the following review, we discuss the cause and consequences of nerve edema with particular reference to endoneuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…As sorbitol is one of the osmolytes that maintain renal homeostasis, an osmoregulatory role of AR was indicated in the kidney (Burg, 1995). It should be noted that the endoneurial fluid electrolytes were reported to fluctuate in accord once with increases in flux of the polyol pathway (Mizisin et al, 1988(Mizisin et al, , 1990. In this context, it is tempting to suggest that sorbitol in Schwann cells may also act as an osmolyte to balance the alterations in endoneurial fluid electrolyte levels in the peripheral nerves of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…As sorbitol is one of the osmolytes that maintain renal homeostasis, an osmoregulatory role of AR was indicated in the kidney (Burg, 1995). It should be noted that the endoneurial fluid electrolytes were reported to fluctuate in accord once with increases in flux of the polyol pathway (Mizisin et al, 1988(Mizisin et al, , 1990. In this context, it is tempting to suggest that sorbitol in Schwann cells may also act as an osmolyte to balance the alterations in endoneurial fluid electrolyte levels in the peripheral nerves of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of proinflammatory cytokines, NO, and ROS extend beyond pathogen killing, because these fibroblastderived substances can also directly increase nerve excitability (160,288,291), damage myelin (202,249,259,283), and/or alter the blood-nerve barrier (83,315). This latter effect leads to edema and infiltration of immune cells, antibodies, and other immune products (198).…”
Section: Anatomy and Immune Surveillancementioning
confidence: 99%
“…The activation of nervi nervorum nervous terminations was implied in peripheral nervous trunk referred pain 25,46,57,58 . Bove and Light 59 have observed that nervi nervourm fibers were arranged in the neural space to respond to induced stimuli during nervous injury such as mechanical compression and tension and are positioned to react to changes of the medium were nervous damages occur, such as those caused by increased subperineural pressure and environmental concentrations of histamine and bradikinin 60,61 . Nervi nervorum and nervi vasorum are vulnerable to nervous tissue injuries resulting from friction and chronic compressive syndromes 56 .…”
Section: Peripheral Neuropathic Pain Pathophysiologymentioning
confidence: 99%